Educational Management Strategies For Improving Student Achievement - Yuni Herlina; Suwarni Suwarni; Feby Elra Perdima; Euis Trianingsih (Lembaga Bale Literasi, 2024)
Educational management is increasingly expected to move beyond administrative compliance and become a strategic mechanism for improving student achievement. This study aims to examine how educational management strategies contribute to student achievement through instructional quality, collaborative teacher culture, and data-informed school improvement. A quantitative explanatory design is proposed, involving senior high school students and teachers selected through proportionate stratified sampling. Data are collected using validated Likert-scale questionnaires, documentation of students’ academic records, and school-level quality assurance indicators. The analytical procedure combines descriptive statistics, confirmatory factor analysis, reliability testing, correlation analysis, and structural equation modeling to evaluate direct and indirect relationships among variables. The illustrative findings indicate that strategic educational management has a positive direct association with student achievement, while its stronger contribution emerges indirectly through instructional coherence, teacher collaboration, and a supportive learning climate. Contrary to established beliefs that student achievement is primarily shaped by classroom-level instructional factors, the proposed model suggests that school-level management capacity functions as an enabling architecture through which instructional improvement becomes systematic, measurable, and sustainable. This study fills the void by integrating instructional leadership theory with distributed leadership and social capital perspectives in one empirical framework. The implications highlight that school leaders should align planning, teacher professional development, learning assessment, stakeholder engagement, and continuous quality assurance as an integrated management strategy rather than fragmented programs. Future studies are encouraged to test the model using longitudinal data and multi-level analysis across different school contexts.